Trắc nghiệm tính chất nguyên hàm

Đề bài: Tìm hàm số (y=f(x)) biết rằng (f'(x) = ({x^2} – x)(x + 1)) và (f(0)=3.) 

Câu hỏi: Tìm hàm số (y=f(x)) biết rằng (f'(x) = ({x^2} – x)(x + 1)) và (f(0)=3.)  A. (y = frac{{{x^4}}}{4} – frac{{{x^2}}}{2} + 3) B. (y = frac{{{x^4}}}{4} – frac{{{x^2}}}{2} – 3) C. (y = frac{{{x^4}}}{4} + frac{{{x^2}}}{2} + 3) D. (y = 3{x^2} – 1) Hãy chọn trả lời đúng trước khi xem đáp án …

Đề bài: Tìm hàm số (y=f(x)) biết rằng (f'(x) = ({x^2} – x)(x + 1)) và (f(0)=3.) Read More »